In Vivo Antitumoral Effects of Linseed Oil and Its Combination With Doxorubicin - Shadyro, Oleg; Sosnovskaya, Anna; Edimecheva, Irina; Ihnatovich, Lana; Dubovik, Boris; Krasny, Sergei; Tzerkovsky, Dmitry; Protopovich, Egor (Frontiers in Pharmacology, 2022)
Linseed oil (LO) is known for its exceptional nutritional value due to the high content of alpha-linolenic acid (ALA), an essential omega-3 polyunsaturated fatty acid; its anticarcinogenic effect has been established in several experimental and epidemiological studies. As an adjuvant of chemotherapeutic agents, LO and other ALA-rich vegetable oils have been studied in only a handful of studies at the experimental level. However, the efficacy of antitumoral therapy using doxorubicin (Dox) in combination with ALA and ALA-rich substrates has not yet been investigated. In this work, the antitumor activity of LO in a wide dose range was studied with monotherapy and combined with Dox in animal models with Pliss lymphosarcoma (PLS) and Lewis lung adenocarcinoma (LLC). It was founded the daily oral administration of LO (100, 300, and 1000 µL per 100 g) to rats (PLS) and 600 µl/100 g to mice (LLC) for 11-12 days from 7 days after subcutaneous transplantation of tumors has a stable statistically significant effect on the dynamics of tumor growth, reducing the intensity of tumor growth and increasing the frequency of complete tumor regressions (CR) compared with the control. LO showed high antimetastatic activity in the LLC model. Furthermore, LO at a dose of 300 µl/100 g potentiates the antitumor effect of Dox in the PLS model, reducing the volume of tumors at the end of treatment by 2.0 times (p = 0.013), the value of the tumor growth index by 1.6 times (p < 0.03) and increasing the frequency of CR 60 days after the start of therapy by 3.5 times (p = 0.019) compared with the use of Dox alone. The combination of Dox and LO or fish oil allows growing efficiency therapy of LLC in comparison with Dox alone, increasing the frequency of CR to 73.68 and 94.4%, respectively, and reducing the frequency of metastasis to zero.